A case of Guillain-Barre syndrome presented with bilateral pseudo-internuclear ophthalmoplegia - Izadi, Sadegh; Sabzgolin, Iman (International Clinical Neuroscience Journal, 2015)
Guillain-Barre syndrome (GBS) or acute idiopathic polyradiculoneuritis is an acquired immune-mediated inflammatory and mainly demyelinating disorder of the peripheral nervous system. Cranial nerves are affected in over 50% of all cases, with the facial nerves being affected the most. It uncommonly presents as atypical forms such as brachial pharyngeal variant, miller fisher and other restricted forms. Herein, we reported a 44 year old male with GBS who presented with diplopia and bilateral pseudo- internuclear ophthalmoplegia. Initially, the patient was confused as a case of multiple sclerosis but finally diagnosis of GBS was made. Although internuclear ophthalmoplegia is a typical feature of multiple sclerosis, it may be seen as a rare manifestation of GBS as well.